METHOD OF MULTIPLE RECALCULATIONS. - O.I. Vejtsblit (Ìнформаційні технології в освіті)
In this work for the analysis of results of integration it is offered a posteriori method of multiple recalculations which is a generalization of a Runge – Richardson method of double recalculation.